The Effect of Iraqi Liquefied Petroleum Gas (LPG) Addition to a Liquid Hydrocarbon Fuels on Emission of an Industrial Furnace Burner - Hadi, Abdul AL-Kadhim M Hasan; Qadir, Sardar Othman (Al-Nahrain Journal for Engineering Sciences, 2017)
The emission sources have great effects on our environment. Further using of fossil fuels because of our needs for heating purposes and developments leads to raising the emission concentration in the air which caused to health risks to human society and its environment. This paper deals with using a different percentage of Iraqi liquefied petroleum gas from 10% to 25% with different percentage of Iraqi Gas-oil fuel from 90% to 75%, keeping the thermal load constant in order to indicate the possibility of reducing the pollutant emissions . A dual fuel burner and equivalence ratio range from 0.8 to 1.4 is used to study the emission concentrations based on these equivalence ratio. For further reducing in emission and heat recovery from the exhaust gases the cooling effect also investigated for water mass flow-rate from 12 kg/s to 48 kg/s roughly. The results showed that for further increasing equivalence ratio the UHC, CO, and Soot increased by about 3% and NOx, and CO2 decreased by 2.5% and this due to decreasing the oxygen ratio in the mixture and incomplete combustion occurred. Also for increasing percentage participating of LPG fuel as a secondary fuel, UHC, CO, and Soot decreased by 8%and NOx and CO2 increased slightly. With heat recovery process the concentration of UHC, CO, and Soot increased slightly while NOx, CO2 decreased by 1.5% because of decreasing of combustion chamber temperature.